Pelatihan Self Management bagi Keluarga dengan Resiko DM Di Desa Kuanheum Kecamatan Kupang Barat Kabupaten Kupang Di Provinsi NTT - Aty, Yoany Maria Vianney Bita; Herawanti, Elisabeth; Nurwela, Trifonia Sri (Universitas Nusantara PGRI Kediri, 2022)
Diabetes Mellitus is a chronic degenerative disease which if not treated seriously will cause serious problems which of course can threaten a person's life. The number of DM sufferers in the village of Kuenheum is 20 people. Sufferers and families explain the lack of information about the management and prevention of diabetes mellitus. The method of community service activities is training for families with DM sufferers. The expected outcome after the implementation of the activity is to increase the family's understanding of DM management. The result of this activity is a family handbook module, which is patented and HKI No. EC00202054759, 1 December 2020. Video uploaded to Youtube and the achievement target of this activity can be 100% carried out well.